2008
DOI: 10.1016/j.jpsychores.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Coping and quality of life in patients awaiting lung transplantation

Abstract: Objective Patients with end-stage lung disease experience significant decrements in quality of life (QOL). Although coping strategies are related to QOL in patients with end-stage lung disease, the extent to which specific native lung disease moderates this relationship is unknown. Methods We investigated the relationship between coping, native lung disease, and QOL among 187 patients awaiting lung transplantation, including 139 patients with chronic obstructive pulmonary disease (COPD) and 48 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 49 publications
2
36
0
7
Order By: Relevance
“…24 Studies found that the following coping strategies: active coping, 25 acceptance of the disease, being optimistic, 26 expression of feelings, 27 positive religious coping, 28 were associated with better quality of life. 29 Other studies revealed that behavioral disengagement, 25 self-blame, 30 high distraction, 26 and negative religious coping, such as a pessimistic view of the world and spiritual discomfort 28 were associated with worse quality of life, in patients with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…24 Studies found that the following coping strategies: active coping, 25 acceptance of the disease, being optimistic, 26 expression of feelings, 27 positive religious coping, 28 were associated with better quality of life. 29 Other studies revealed that behavioral disengagement, 25 self-blame, 30 high distraction, 26 and negative religious coping, such as a pessimistic view of the world and spiritual discomfort 28 were associated with worse quality of life, in patients with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety (35%), depression (19%) and panic attacks (63%) are reported to be higher in patients with chronic obstructive pulmonary disease (COPD) as they suffer from more disruptive respiratory symptoms. Consequently, a thorough evaluation of the combined effects of physical and psychological aspects should be part of the pre-transplantation follow-up (Taylor et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…In lung patients, disengagement is associated with depression, anxiety and stress (Taylor et al, 2008). In heart-transplant-awaiting patients, denial and depression correlate with poor adaptive ability (Burker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tal es el caso de las investigaciones realizadas en pacientes con epilepsia (Endermann & Zimmermann, 2009), diversos tipos de cáncer (Gaviria et al, 2007;Costa Neto, & Cavalcanti, 2005); enfermedad pulmonar obstructiva crónica EPOC (Taylor et al, 2008;Vinaccia et al, 2006b;Pérez et al, 2005); insuficiencia renal crónica (Contreras et al, 2007;Pucheu, et al, 2004); pacientes con fallas cardiacas y enfermedades cardiovasculares crónicas (Krethong et al, 2007); hiperplasia prostática (Vinaccia et al, 2006a); dispepsia no ulcerosa (Cano et al, 2006); fibrosis quística (Abbott et al, 2008); diabetes mellitus tipo 2 (Pirkola et al, 2009), y pacientes con dolor crónico (Taylor, Dean, & Siegert, 2006). En el campo de la salud mental se ha estudiado la calidad de vida y la calidad de vida relacionada con la salud en pacientes diagnosticados con esquizofrenia (Awad, Voruganti, & Heslegrave, 1997;Caqueo & Lemos, 2008;Narváez et al, 2008); desorden obsesivo compulsivo (Albert et al, 2009), y diagnóstico de depresión (Gallegos et al, 2009).…”
unclassified
“…En relación con variables psicológicas se ha encontrado que el afrontamiento es un factor que determina significativamente la calidad de vida en personas con discapacidad o en condiciones crónicas de enfermedad (Abbott et al, 2008;Cano et al, 2006;Contreras et al, 2007;Gaviria et al, 2007;Groot & Van Den Brink, 2007;Desmond & MacLachlan, 2006;Taylor et al, 2008;Velasco & Londoño, 2010;Vinaccia, et al, 2006b). En las personas con discapacidad física, así como en otros grupos poblacionales, pueden existir diferencias importantes en los estilos de afrontamiento utilizados para adaptarse a problemas y dificultades relacionadas con la discapacidad y con la vida diaria.…”
unclassified